2017
DOI: 10.1016/j.appet.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Individual, behavioural and home environmental factors associated with eating behaviours in young adolescents

Abstract: This study aimed to examine individual, behavioural and home environmental factors associated with frequency of consumption of fruit, vegetables and energy-dense snacks among adolescents. Adolescents aged 11–12 years (n = 521, 48% boys) completed a paper-based questionnaire during class-time which included a Food Frequency Questionnaire assessing their consumption of fruit, vegetables, and energy-dense (ED) snacks, and items assessing habits, self-efficacy, eating at the television (TV), eating with parents, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 41 publications
4
65
0
7
Order By: Relevance
“…Another mechanism that could potentially explain our findings is the clustering of food parenting practices. Illustratively, parents who serve as healthy role models for their children's food intake, also use other structured food parenting practices (e.g., rules, home food availability, and boundaries) [45][46][47][48] that may explain healthy food intake similarities between mothers and their children. Additionally, since previous studies have shown that food preference and intake are influenced by genetic factors [49][50][51], food intake similarities between mothers and their children could also be due to genetic resemblance.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism that could potentially explain our findings is the clustering of food parenting practices. Illustratively, parents who serve as healthy role models for their children's food intake, also use other structured food parenting practices (e.g., rules, home food availability, and boundaries) [45][46][47][48] that may explain healthy food intake similarities between mothers and their children. Additionally, since previous studies have shown that food preference and intake are influenced by genetic factors [49][50][51], food intake similarities between mothers and their children could also be due to genetic resemblance.…”
Section: Discussionmentioning
confidence: 99%
“…Five response categories were available: (i) never/I don't eat (fruit), (ii) less than one portion a day, (iii) 1-2 portions a day, (iv) 3-5 portions a day, (v) 5 or more portions a day. The frequency of food consumption was converted to a daily equivalent, which is an established method that has been used successfully in other dietary studies [35]. The frequency of consumption of the four food categories was converted to a continuous daily equivalents as follows: never (0 per d); less than one portion a day (0 •5…”
Section: Eating Behavioursmentioning
confidence: 99%
“…Children were asked four questions about their habits for eating snack foods in front of the television using the valid Self-Report Behavioural Automaticity Index (SRBAI) [36], which has been successfully used in children of this age [35]. They were asked the same four questions regarding eating sweet and savoury snacks, eating fruit and vegetables as a snack, eating fruit and vegetables in front of the TV, and regarding habit for watching TV.…”
Section: Secondary Outcomes Individualmentioning
confidence: 99%
“…Knowledge of adolescents' fish consumption is very limited, but is certainly less than government recommendations (Groot, Ouwehand & Jolles, 2012) and probably less than that of the general population, since for example, it is known that individuals aged 16-24 years are less likely than other age groups to meet the five-a-day recommendation for fruit and vegetables (Mintel, 2012). It has been shown that adolescents often eat snacks, especially in front of the TV, and given the availability of both healthier snacks containing fruit or vegetables, and energy-dense snacks, they tend to prefer the latter (Pearson et al, 2016). Parents have been shown to have a more positive attitude towards fish products than adolescents (Olsen et al, 2008), and this may be partly due to them tending to have a better understanding of the principles of healthy eating (Laguna-Camacho & Booth, 2015).…”
Section: Adolescents and Fish Consumptionmentioning
confidence: 99%